The novel of "Simorgh" by Mohamed Dib: Reading from a cultural perspective - Yakoubi, Nassima (Journal of Human Sciences, 2023)
The literary critical discourse is the science in which self-comfort is appeared, where the speaking self is absent and the conversation is about the other, not about the self, and then the critical discourse grew, developed, diversified and opened up to other cultures since Aristotle whom they made a first teacher to what is going on today in the global critical culture.Therefore, the self and its loss is, in fact, nothing but a pretext to invest values in order to live, develop, and open up to others, and to different cultures and civilizations. In this text, Mohammed Dib performs a symbolic practice through the imagination and reconstructs reality and presents it in the form of linguistic patterns. The text of Simurgh is an oriental myth that calls for reading and looking at other cultures, and reveals the ideological meaning of its owner.